2021
DOI: 10.1016/j.drugalcdep.2020.108345
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant drugs with buprenorphine user deaths

Abstract: Background: Buprenorphine is abused in several countries notwithstanding its benefits as an analgesic and as an opioid agonist treatment medication. Benzodiazepines and alcohol have previously been associated with buprenorphine toxicity. This study elucidates the role of emerging concomitant drugs in different groups of buprenorphine user deaths. Methods: All cases in the Finnish national post-mortem toxicology database from 2016-2019 in which buprenorphine or norbuprenorphine was a laboratory finding in any p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
2
21
1
1
Order By: Relevance
“…The results show high concomitant use of primarily benzodiazepines in buprenorphine poisonings and indicate an increase in buprenorphinerelated deaths, especially among younger individuals. The study did not examine the proportion among the deceased who had prescriptions of buprenorphine or experience of OST [58]. The results of these, and other, studies illustrate a current increase in deaths related to OST-medications.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results show high concomitant use of primarily benzodiazepines in buprenorphine poisonings and indicate an increase in buprenorphinerelated deaths, especially among younger individuals. The study did not examine the proportion among the deceased who had prescriptions of buprenorphine or experience of OST [58]. The results of these, and other, studies illustrate a current increase in deaths related to OST-medications.…”
Section: Discussionmentioning
confidence: 94%
“…Only a few individuals had been prescribed methadone the year before the death, which indicates that the increasing trend was mainly a result of an increased exposure to non-prescribed methadone among younger opioid users [57]. Another recent study by Mariottini and colleagues [58] investigated buprenorphine-related deaths in Finland 2016-2019. The results show high concomitant use of primarily benzodiazepines in buprenorphine poisonings and indicate an increase in buprenorphinerelated deaths, especially among younger individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids were the main cause of death but as well as heroin/ morphine, included methadone, buprenorphine and fentanyl analogues (Simonsen et al, 2020). Similarly, the analysis of a Finnish national post-mortem toxicology database showed that there were no death cases with buprenorphine as the only toxicological finding, with concomitant benzodiazepines commonly detected (Mariottini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the relative safety of BUP and methadone for OAT revealed that BUP was six times safer than methadone regarding overdose risk in the general population 24 . Despite its relative safety, accidental and intentional BUP toxicity deaths still occur among both OAT patients and opioid users outside of treatment, with intravenous injection and concomitant sedative drug use being recognized as risk factors 25,26 . Even the combination product BUP/NAL is liable to misuse and fatal poisonings 27,28 …”
Section: Introductionmentioning
confidence: 99%
“…24 Despite its relative safety, accidental and intentional BUP toxicity deaths still occur among both OAT patients and opioid users outside of treatment, with intravenous injection and concomitant sedative drug use being recognized as risk factors. 25,26 Even the combination product BUP/NAL is liable to misuse and fatal poisonings. 27,28 Within therapeutic drug monitoring and toxicology, laboratory analysis of BUP and its metabolites is used to monitor adherence and to reveal BUP toxicity.…”
Section: Introductionmentioning
confidence: 99%